Metropolitan government and economic development - Carr, Jered B.; Feiock, Richard C. (1999)
Academic and political debate regarding the desirability of metropolitan government has focused on the provision of public goods. Although efficient production of services is of great importance, the consequences of metropolitan government for economic development have remained unexplored. The authors assess the development impacts of city-county consolidation by examining the attraction of manufacturing and retail/service firms for nine consolidated governments from 1950 to 1993. The annual growth in manufacturing, retail, and service establishments in the county before the merger is compared to the record afterward. No support emerges for the idea that consolidation enhances economic development. - Reproduced
Keywords: Economic and social development